2008
DOI: 10.1074/jbc.m800298200
|View full text |Cite
|
Sign up to set email alerts
|

Organic Anion Transporter OAT1 Undergoes Constitutive and Protein Kinase C-regulated Trafficking through a Dynamin- and Clathrin-dependent Pathway

Abstract: Organic anion transporter 1 (OAT1) mediates the body disposition of a diverse array of environmental toxins and clinically important drugs. Therefore, understanding the regulation of this transporter has profound clinical significance. We previously demonstrate that OAT1 activity was down-regulated by activation of protein kinase C (PKC), kinetically revealed as a decrease in the maximum transport velocity V max without significant change in the substrate affinity K m of the transporter. In the current study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
121
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(133 citation statements)
references
References 51 publications
10
121
0
Order By: Relevance
“…PKC activation decreased surface levels of OAT1, OAT4, OATP2B1, and OATP1A2 without affecting total protein levels of these transport proteins after short-term treatment with a PKC activator for up to 1 hour (Zhou et al, 2007(Zhou et al, , 2011Zhang et al, 2008Zhang et al, , 2010Köck et al, 2010). Rapid downregulation of transport function by PKC activation is associated with increased phosphorylation of OATP2B1 (Köck et al, 2010), the brain glutamate/aspartate transporter GLAST-1 (Conradt and Stoffel, 1997), as well as dopamine (Huff et al, 1997) and serotonin transporters (Jayanthi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PKC activation decreased surface levels of OAT1, OAT4, OATP2B1, and OATP1A2 without affecting total protein levels of these transport proteins after short-term treatment with a PKC activator for up to 1 hour (Zhou et al, 2007(Zhou et al, , 2011Zhang et al, 2008Zhang et al, , 2010Köck et al, 2010). Rapid downregulation of transport function by PKC activation is associated with increased phosphorylation of OATP2B1 (Köck et al, 2010), the brain glutamate/aspartate transporter GLAST-1 (Conradt and Stoffel, 1997), as well as dopamine (Huff et al, 1997) and serotonin transporters (Jayanthi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The function of several human transport proteins is regulated by PKC activation. For example, PKC activation downregulates transport function of organic anion transporter (OAT) 1 (Zhang et al, 2008), OAT3 (Duan et al, 2010), and OAT4 (Zhou et al, 2007;Zhang et al, 2010); OATP2B1 (Köck et al, 2010) and OATP1A2 (Zhou et al, 2011); efflux transport protein P-glycoprotein (P-gp) (Miller et al, 1998); and multidrug resistance protein (MRP)2 (Kubitz et al, 2001). OATP1B3 has putative PKC phosphorylation sites as predicted by Scansite 3 (Obenauer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PKCa was mobilized to the plasma membrane after angiotensin II treatment, and inhibition of PKCa prevented internalization of hOAT1 [103]. In a complementary study, it was demonstrated that hOAT1 is constitutively internalized and recycled back into the plasma membrane [104]. Activation of PKC increased the internalization of hOAT1 without a concomitant increase in recycling, the net effect of which was a reduction in hOAT1 expression in the plasma membrane in response to PKC activation.…”
Section: Phosphorylationmentioning
confidence: 96%
“…Activation of PKC increased the internalization of hOAT1 without a concomitant increase in recycling, the net effect of which was a reduction in hOAT1 expression in the plasma membrane in response to PKC activation. Interestingly, inhibition of clathrin-dependent endocytosis reduced hOAT1 internalization, clearly indicating a role for clathrin-coated pits in this process [104]. The studies discussed above demonstrated a consistent suppressive role for PKC, including PKCa, in the regulation of Oat1, but a recent investigation challenged this generalization of PKC's role.…”
Section: Phosphorylationmentioning
confidence: 96%
See 1 more Smart Citation